Diselenide mediated controlled radical polymerization under visible light irradiation: mechanism investigation and α, ω-ditelechelic polymers1. Issue 35 (21st September 2015) - Ding, Chunlai; Fan, Caiwei; Jiang, Ganquan; Zhang, Jiandong; Li, Xiaohong; Li, Na; Pan, Xiangqiang; Zhang, Zhengbiao; Zhang, Wei; Zhu, Jian; Zhu, Xiulin
<x xml:space="preserve">Abstract</x> The radical polymerization of styrene was investigated in the presence of five diaryl diselenide compounds with different groups on the benzene ring under visible light irradiation.